Crack initiation characteristics and fatigue property of a high-strength steel in VHCF regime under different stress ratios (Fracture and Structural Integrity, 2015)
Crack initiation characteristics and fatigue property of a high-strength steel in very-high-cycle fatigue (VHCF) regime under different stress ratios were investigated in this paper. Fatigue tests were performed at stress ratios of -1, -0.5, 0.1 and 0.3 by using an ultrasonic fatigue testing machine. The difference of S-N data and the characteristics of crack initiation under different stress ratios were examined. It is shown that the magnitude of stress ratio has a substantial effect on the fatigue strength that decreases with the increase of stress ratio. However, the variation tendency of the S-N data from low-cycle fatigue to VHCF regime is similar for the four cases. SEM observations of the fracture surface indicate that fatigue crack initiates from the surface of specimen in low-cycle regime and initiates mostly from the inclusion in the interior of specimen in high-cycle and VHCF regimes, which is irrespective of the state of stress ratio. By means of Focused Ion Beam technique, the samples of crack initiation region were prepared then observed via TEM. The observations show the microscopic morphology of the crack initiation region, showing the different crack initiation characteristics and revealing the mechanism of crack initiation for different stress ratios. Moreover, the effect of inclusion size on fatigue life is discussed with the results showing that the effect of stress ratio and inclusion size on fatigue strength is well described by our proposed formula.
Keywords: High-strength steel; Very-high-cycle fatigue; Crack initiation characteristics; Stress ratio; Inclusion size